Porous niobium nitride as a capacitive anode material for advanced Li-ion hybrid capacitors with superior cycling stability. Issue 25 (13th June 2016) - Wang, Peiyu; Wang, Rutao; Lang, Junwei; Zhang, Xu; Chen, Zhenkun; Yan, Xingbin
Abstract : Lithium-ion hybrid capacitors (LIHCs) are receiving intense interest because they can combine the distinctive advantages of Li-ion batteries and supercapacitors. Abstract : Lithium-ion hybrid capacitors (LIHCs) are receiving intense interest because they can combine the distinctive advantages of Li-ion batteries and supercapacitors. Their main limitations, however, are slow anode kinetics and poor cycle life when compared to supercapacitors. Here we demonstrate for the first time that conductive porous niobium nitride (p-NbN) with a cubic crystal structure, one-step prepared from commercial powdery Nb2 O5, is an ideal anode material having pseudocapacitive characteristics (high rate lithium ion storage and excellent long-term cycling stability) for LIHCs. As a consequence, a novel LIHC is fabricated using p-NbN as the anode and activated carbon as the cathode. This device with a wide potential window of 4.0 V exhibits a high energy density of 149 W h kg −1 and a high power density of 45 kW kg −1 as well as a superior capacity retention of 95% after 15 000 cycles at 1.0 A g −1 . In view of the excellent electrochemical characteristics, the simple manufacturing of p-NbN as well as the high-density nature of the NbN material, our results are of great importance for future development of long-life LIHCs with high gravimetric/volumetric performances.